"No Silver Bullet Solution": Cruel Optimism and Canada’s COVID-19 Public Health Messages - Holmes, Christina; Krautwurst, Udo; Graham, Kate; Fernandez, Victoria (Anthropologica, 2021)
Science twines through many of the discussions related to hope for a return to normalcy within public discussions of COVID‑19. The framings of techno-scientific solutions for COVID‑19 are similar to those that are presented to address many societal problems. The messy scientific and regulatory underpinnings of this desired silver bullet rarely make it fully into view. Technoscientific-related hope and its associated affects can operate as a kind of “cruel optimism” (Berlant 2010, 2011). It can be an affective response to return to life as “normal” that is psychologically soothing, even as its enactment may replicate destructive social, political, and economic structures. Hope and technoscience thread throughout the interactions between journalists and health officials in the health press briefings in the first wave of the COVID‑19 pandemic. Technoscientific complexity that challenges the desire to return to normal is rarely brought up in Ontario and Nova Scotia public health briefings. But when it is, health officials in this zone of interaction balance explanations of scientific reality and caution, while attempting to not crush hope for a techno-scientifically mediated return to normal. As such, public health discourse obscures or tempers cruel optimism rather than directly confronting it.